Sistem Pakar Diagnosis Anxiety Disorder Dengan Metode Forward Chaining Berbasis Web - Shaela, Pamela; Sugianti, Devi; Syaifudin, Anas; Darmawan, Arief Soma; Risqiati, Risqiati (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Anxiety Disorders are the most common mental health disorders in the world. The 2018 Indonesian Health Research Main Results showed a significant increase in the prevalence of mental disorders. However, the comparison of the number of Indonesian people with professional psychology personnel is still very unbalanced and far from the WHO standard which requires the ratio of experienced mental health personnel to the ideal population of 1:30,000. Pekalongan City only has 6 clinical psychologists with a population of 317,958 people. So many people with mental health disorders do not receive adequate treatment. To overcome this problem, a web-based expert system was developed that can diagnose anxiety disorders using the forward chaining method, which imitates the thought process of an expert in making decisions based on symptom data and certain rules. This system was developed using the waterfall method, which includes needs analysis, system design, implementation, integration, testing, and maintenance. Testing was carried out using the White Box, Black Box, and User Acceptance Test (UAT) methods. Data for the UAT test was obtained by involving 100 respondents from Pekalongan City, who were selected using the Simple Random Sampling method and calculated using the Slovin Formula to ensure adequate representation. UAT results showed that respondents “strongly agreed” that the system was easy to use, informative, and useful in providing an initial understanding of anxiety disorders and the importance of mental health.